Comparative biokinetics and metabolism of pure monomeric, dimeric, and polymeric flavan‐3‐ols: A randomized cross‐over study in humans. Issue 4 (18th February 2015) - Wiese, Stefanie; Esatbeyoglu, Tuba; Winterhalter, Peter; Kruse, Hans‐Peter; Winkler, Stephanie; Bub, Achim; Kulling, Sabine E.
<x xml:space="preserve">Abstract</x> Scope Flavan‐3‐ols are abundant polyphenols in human nutrition and are associated with beneficial health effects. The aim of this study was to comparatively investigate the metabolic fate of (‐)‐epicatechin, procyanidin B1, and polymeric procyanidins in a randomized cross‐over study in humans. Methods and results Parent compounds, conjugates, and microbial metabolites were determined in plasma, urine, and faeces by HPLC‐MS and GC‐MS/MS. Glucuronidated, sulfated, and methylated (‐)‐epicatechin and 5‐(3′, 4′‐dihydroxyphenyl)‐valerolactone were the dominant metabolites in blood and urine. In addition, minor amounts of procyanidin B1 and 4‐hydroxy‐5‐(3′, 4′‐dihydroxyphenyl)valeric acid and their conjugated metabolites were detected. The formation of 5‐(3′, 4′‐dihydroxyphenyl)‐valerolactone and 4‐hydroxy‐5‐(3′, 4′‐dihydroxyphenyl)valeric acid varied largely between individuals as well as with the degree of polymerization of flavan‐3‐ols. Monomer units were not detectable in plasma or urine after procyanidin B1 and polymeric procyanidin intake. No correlation was found between the intake of flavan‐3‐ols and the occurrence of phenolic acids in blood and urine or the phenolic compound profiles in faeces. Conclusion In addition to conjugated metabolites derived from the absorption of monomeric flavan‐3‐ols, 5‐(3′, 4′‐dihydroxyphenyl)‐valerolactone represents an important in vivo metabolite of (‐)‐epicatechin and procyanidin B1 produced by the gut microbiota.